The Enginering Important Components of Jatibarang Dam, Semarang, Indonesia - Jonathan PLANCHOT; Maxime LENOIR; S. Imam Wahyudi; Fateh BENDAHMANE; Henny Pratiwi Adi (International Conference on Coastal and Delta Areas, 2015)
Semarang City suffers from inundation caused by storm rainfall and high tide due to its low-lying topography along the coastal area. The Jatibarang Dam purpose is to develop a new source of water for Semarang City and to control the flood discharge of West Floodway as the biggest river in Semarang. Also, it has been recognized that the combination of the Jatibarang Dam and the rivers improvement is the most feasible flood control measure. The flood control scheme will be established to protect Semarang City from the 50-year return period flood and the water resources development scheme is planned to assure the water to the 10-year draught. The design flooding will be controlled by the Jatibarang Dam. About 270 m3/s of 50-year return period flood at Jatibarang dam will be controlled by the dam and the discharge from dam will be reduced to 100 m3/s. The Engineering important components of the Dam are diversion tunnel, dam structure, spillway and conduit of power works.Each component will be elaborated in this article.